Morphology and Molecular Composition of Purified Bovine Viral Diarrhea Virus Envelope. - Nathalie Callens; Britta Brügger; Pierre Bonnafous; Hervé Drobecq; Mathias J Gerl; Thomas Krey; Gleyder Roman-Sosa; Till Rümenapf; Olivier Lambert; Jean Dubuisson; Yves Rouillé (PLoS Pathogens)
The family Flaviviridae includes viruses that have different virion structures and morphogenesis mechanisms. Most cellular and molecular studies have been so far performed with viruses of the Hepacivirus and Flavivirus genera. Here, we studied bovine viral diarrhea virus (BVDV), a member of the Pestivirus genus. We set up a method to purify BVDV virions and analyzed their morphology by electron microscopy and their protein and lipid composition by mass spectrometry. Cryo-electron microscopy showed near spherical viral particles displaying an electron-dense capsid surrounded by a phospholipid bilayer with no visible spikes. Most particles had a diameter of 50 nm and about 2% were larger with a diameter of up to 65 nm, suggesting some size flexibility during BVDV morphogenesis. Morphological and biochemical data suggested a low envelope glycoprotein content of BVDV particles, E1 and E2 being apparently less abundant than Erns. Lipid content of BVDV particles displayed a ~2.3 to 3.5-fold enrichment in cholesterol, sphingomyelin and hexosyl-ceramide, concomitant with a 1.5 to 5-fold reduction of all glycerophospholipid classes, as compared to lipid content of MDBK cells. Although BVDV buds in the endoplasmic reticulum, its lipid content differs from a typical endoplasmic reticulum membrane composition. This suggests that BVDV morphogenesis includes a mechanism of lipid sorting. Functional analyses confirmed the importance of cholesterol and sphingomyelin for BVDV entry. Surprisingly, despite a high cholesterol and sphingolipid content of BVDV envelope, E2 was not found in detergent-resistant membranes. Our results indicate that there are differences between the structure and molecular composition of viral particles of Flaviviruses, Pestiviruses and Hepaciviruses within the Flaviviridae family.